PENGEMBANGAN E-MODUL BERBASIS PEMECAHAN MASALAH UNTUK SEKOLAH MENENGAH ATAS SEBAGAI UPAYA DALAM MELATIH KETERAMPILAN PROSES SAINS - Artha Lumbantoruan; Muhaimin Muhaimin; Sri Purwaningsih (JURNAL SPEKTRA, 2022)
Science process skills (SPS) have an essential role in science learning. However, based on the analysis results, the achievement of SPS at SMA Negeri 11 Jambi City tends to be low. The lack of relevant learning resources is one of the factors influencing efforts to train SPS. This study aims to develop an electronic module (e-module) based on problem-solving skills by considering the implementation of the fundamental SPS indicators and the integrated SPS in it. The development model used is Lee and Owens type ADDIE, carried out in small groups until the evaluation stage. The test subjects consisted of 20 students in class XI science and one physics teacher. The data collected is qualitative and analyzed by triangulation and spiral methods. The development results show that the e-module has the potential to train SPS students because it has met the valid criteria conceptually and procedurally.